2007
DOI: 10.1111/j.1398-9995.2007.01397.x
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of symptom‐based definition of chronic rhinosinusitis

Abstract: It is well established that symptoms are very important in the diagnosis of CRS. However, two major symptoms are insufficient for diagnosis. Therefore, endoscopy and CT have important differential diagnostic roles. Our study showed that in patients with three major symptoms, CT pathology may be sufficient for definitive diagnosis. However, in patients with two major symptoms such as nasal discharge and/or low grade nasal polyposis, endoscopy becomes considerably more important due to inspective findings. If no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 15 publications
3
23
1
1
Order By: Relevance
“…The same symptom structure was reported by Montnémery and colleagues, 9 although assessed by different methods. A strong positive correlation between SNAQ-11 scores and endoscopic scores was found in our study and is in opposition to the results of Tahamiler and colleagues, 21 who found that 75% of patients with symptom-based diagnosis of chronic nonallergic rhino-sinusitis had no endoscopic pathology. Similar doubts on the value of symptom-based diagnosis of chronic rhinosinusitis have been raised by others.…”
Section: Discussioncontrasting
confidence: 99%
“…The same symptom structure was reported by Montnémery and colleagues, 9 although assessed by different methods. A strong positive correlation between SNAQ-11 scores and endoscopic scores was found in our study and is in opposition to the results of Tahamiler and colleagues, 21 who found that 75% of patients with symptom-based diagnosis of chronic nonallergic rhino-sinusitis had no endoscopic pathology. Similar doubts on the value of symptom-based diagnosis of chronic rhinosinusitis have been raised by others.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the entity is rarely discussed in pediatric medicine, although upper respiratory complaints are common. The diagnosis of chronic rhinosinusitis cannot be made on the grounds of symptoms only (22). Epidemiologic data based on questionnaires for chronic rhinosinusitis are therefore limited and difficult to assess.…”
Section: Magnitude Of the Problemmentioning
confidence: 99%
“…Although CRS is not a lifethreatening disease, it can significantly decrease patientÕs QoL (8)(9)(10). Quality of life is a very important outcome in the evaluation of CRS severity and its measurements reflect the effect that symptoms and disease have on the patientÕs daily life (11). However, it is of interest that the presence and/or severity of nasal symptoms do not always correlate with QoL questionnaires (12).…”
mentioning
confidence: 99%